Estudios mastozoológicos colombianos, ii (1966)
This is a second contribution to the systematic and zoogeographical knowledge of the Colombian mammals. Sciurus (Guerlinguetus) aestuans georgihernandezi (new subsp.) is described from the vicinity of Mitú, Vaupés, at the right bank of the Vaupés River. It might be recognized by the absence of light postauricular patches, besides the upperparts are darker, and the lower ones are lighter than in S. a. gilvigularis, and the tips of the hairs in the tail are white instead of ochraceous (or xanthine) orange. A specimen from the opposite bank of the Vaupés River (collected at Cubiyú Savanna) is referred to S. a. gilvigularis, a taxon previously unrecorded from Colombia. However it is noteworthy that the Vaupés River acts here as a barrier between the ranges of both subspecies, but the Rio Negro, as well as other large rivers of the Brazilian Amazonian are not barriers for subspecies of S. aestuans.  The brown brocket of the Macarena Mountains is named Mazama gouazoubira medemi It is strikingly lighter than M. g. murelia, its closest geographical relative, so that it resembles M. g. cita from Northern Colombia and Venezuela, but it mainly differs in chromatic details, as well as by its larger lachrymal bone.